Fight or flight: integral emotions and violent intentions - Barnum, Timothy C. (Criminology, 2019)
The effect of proximate emotions on risk perceptions is of central importance to criminal decision‐making theory, but has been understudied. We investigate the role of two integral (situational specific) emotional responses, anger and fear, in a decision‐making context regarding the choice to commit assault. We draw on dual‐process models of information processing and appraisal theory to propose a theoretical model in which integral emotions influence decisions and behavior. Using data from an experiment embedded in a survey to a nationwide sample of adults (N = 804), we test the interrelated roles of anger, fear, and traditional rational choice considerations on the intention to commit assault. We find a strong direct association between emotions and intentions to commit assault. Additionally, anger and fear moderate the effect of cognitive deliberations on behavioral intentions and provide a lens through which to evaluate a criminogenic opportunity.